MEMBONGKAR KONSEP ETIKA BISNIS DALAM AL-QURâ€™AN: SEBUAH PERSPEKTIF EPISTEMOLOGIS - Ahmad Syukron (Religia, 2009)
In Islamic economics discipline, Islamic business ethic is a guidance to do business based on values that consist in Qurâ€™an. The appearance of Islamic business ethic, as a matter of fact, plays very important role in changing assumption and understating of â€œamoral business system thoughtâ€, which glows in social life at present. By the appearance of Islamic business ethic, it is expected that business is no longer viewed as amoral activity that ignore ethical values.